2004
DOI: 10.1007/s00464-003-8211-0
|View full text |Cite
|
Sign up to set email alerts
|

Totally extraperitoneal (TEP) hernia repair after an original TEP

Abstract: We have found that TEP repair of recurrent inguinal hernia after a primary TEP repair is entirely feasible technically as well as entirely safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
3
14
0
1
Order By: Relevance
“…A TEP repair is also particularly difficult and complication-prone following transabdominal urinary bladder or prostate surgery, as we have to expect serious preperitoneal scarring in these cases too. In contrast, Ferzli et al [22] reported for the first time on a re-TEP repair, also describing special difficulty in the preperitoneal dissection, however.…”
Section: Tep Techniquementioning
confidence: 83%
“…A TEP repair is also particularly difficult and complication-prone following transabdominal urinary bladder or prostate surgery, as we have to expect serious preperitoneal scarring in these cases too. In contrast, Ferzli et al [22] reported for the first time on a re-TEP repair, also describing special difficulty in the preperitoneal dissection, however.…”
Section: Tep Techniquementioning
confidence: 83%
“…In these reports, several authors reported the feasibility of TAPP repair for recurrence after primary laparoscopic hernia repair by TAPP or TEP. 8 7 Twenty patients had recurrent hernia and underwent TEP. In these patients, 12 hernias were on the ipsilateral side, and 8 were on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Some studies reported that recurrence rates ranged from 0.3% to 8.5%, 5 and the rate of contralateral occurrence was about 1%. 6,7 As the period of postoperative surveillance is extended, it is thought that the number of patients with recurrence or with a new hernia on the contralateral side will increase.…”
Section: Introductionmentioning
confidence: 99%
“…Scheurlein et al [12] conducted laparoscopic TEP hernia repair on 179 patients with recurrent inguinal hernia and reported a 0.4% recurrence rate. Ferzil et al [13] reported that they found no technical or safety issue in the application of the TEP approach to patients who showed recurrence after laparoscopic TEP hernia repair. Despite a smaller subject size and a follow-up period of less than five years, these authors conducted laparoscopic TEP hernia repair on 191 patients with inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%